Pelatihan Teknik Penyusunan Presentasi Produk atau Ide Bisnis Untuk Siswa SMK Negeri 1 Sukawati - Ni Made Satvika Iswari (I-Com: Indonesian Community Journal, 2024)
Entrepreneurship is an important competency in the current era of globalization. An entrepreneur must be able to convey his business vision and ideas clearly to other people, including potential investors, partners or customers. A product or business idea presentation is a platform to communicate the vision and ideas of this business in a convincing way. Presenting a product or business idea has a number of benefits that are very important for the success of a company. Presentations can provide an opportunity to introduce a product or business idea to an audience. By effectively utilizing product or business idea presentations, companies can increase their chances of success, generate interest from potential customers and partners, and build strong relationships in the marketplace. Through this community service activity, training will be provided on product presentation techniques or business ideas for students at SMK Negeri 1 Sukawati. It is hoped that the training carried out will provide the practical knowledge and skills needed to start and accelerate a business, and can help students understand how to make effective presentations for products or business ideas.